The Role of Trust in Mexican Companies in Relation to the Human Factor - de la Garza Carranza, María Teresa; López-Lemus, Jorge Armando; Guzmán Soria, Eugenio; Vargas Chanes, Delfino (Organizations and Markets in Emerging Economies, 2019)
The purpose of this study is to analyze the role of trust in Mexican companies in relation to organizational factors, the leadership and career satisfaction of employees. To achieve this objective, a quantitative method of structural model equations was used. The sample consisted of 181 individuals working in service businesses, manufacturing and public service mainly. The study was done in the central part of Mexico. The study results show a positive correlation of trust of employees towards their managers related with benevolence and integrity. With regard to the relation with organizational factors, a strong relationship was found between trust and leadership but not with the policies related to management of employees. Finally, a weak relationship between leadership and career satisfaction of employees was confirmed. Through the model analyzed, it can be stated that the culture plays an important role for the development of trust in organizations. Also, recommendations for policy makers, such as ways of increasing feedback through employees, are presented.